Growth, Inequality and Race in Singapore - PANG, Eng Fong (Institutional Knowledge at Singapore Management University, 1975)
Examines the overall degree of income inequality, economic growth and differences between major occupational and ethnic groups in Singapore. Conclusion on the single-minded concentration on growth.